A Cu/ZnO Nanowire/Cu Resistive Switching Device - Li, Lijie; Zhang, Yan; Chew, Zhengjun (Nano-Micro Letters, 2013)
A new device has been realized using flip-chip joining two printed circuit boards (PCBs) on which zinc oxide (ZnO) nanowires were synthesized. Energy dispersive X-ray measurement has been conducted for the ZnO nanowires, confirming that Cu elements have been diffused into the nanowires during the chemical growth process. From I–V measurements, this Cu/ZnO nanowire/Cu structure exhibits a resistive tuning behaviour, which varies greatly with the frequency of the applied sinusoidal source.